2010
DOI: 10.1007/s11248-010-9403-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms among C57BL/6 mouse inbred strains

Abstract: Mice from the inbred C57BL/6 strain have been commonly used for the generation and analysis of transgenic and knockout animal models. However, several C57BL/6 substrains exist, and these are genetically and phenotypically different. In addition, each of these substrains can be purchased from different animal providers and, in some cases, they have maintained their breeding stocks separated for a long time, allowing genetic differences to accumulate due to individual variability and genetic drift. With the aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
149
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(159 citation statements)
references
References 10 publications
7
149
1
2
Order By: Relevance
“…C57BL/6 substrains are often considered interchangeable, and a lack of reference to which specific substrain was used is common in experimental methodologies. However, there is growing awareness of the significant genetic and phenotypic differences between even closely related mouse strains and substrains (19,(26)(27)(28), and the present study demonstrates the complete absence in a C57BL/6 substrain of what is generally considered a ubiquitous plasticity mechanism in both mice and rats (14,16,20,29). This finding underscores the importance of reporting mouse background substrains and of using appropriate littermate controls.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…C57BL/6 substrains are often considered interchangeable, and a lack of reference to which specific substrain was used is common in experimental methodologies. However, there is growing awareness of the significant genetic and phenotypic differences between even closely related mouse strains and substrains (19,(26)(27)(28), and the present study demonstrates the complete absence in a C57BL/6 substrain of what is generally considered a ubiquitous plasticity mechanism in both mice and rats (14,16,20,29). This finding underscores the importance of reporting mouse background substrains and of using appropriate littermate controls.…”
Section: Discussionsupporting
confidence: 65%
“…The most prominent genetic difference between the two substrains is the absence of α-synuclein in 6JOla mice; however, we have shown that this protein is not required for the homeostatic component of OD plasticity. The numerous other genetic differences between the two substrains include other absent or mutated genes and a multitude of copy number variations (26,27,30). The analysis of these differences may allow identification of a unique molecular mechanism of homeostatic plasticity as more is discovered about the signaling pathways involved.…”
Section: Discussionmentioning
confidence: 99%
“…Since its establishment, the C57BL/6 inbred strain has led to the origin of several substrains, which differ genetically and phenotypically with respect to the reference C57BL/6J [8]. To verify the genetic makeup of the Prnp ZH3/ZH3 mouse line, we analyzed 12 SNPs known to be informative among different C57BL/6 substrains.…”
Section: Methodsmentioning
confidence: 99%
“…Mice may differ in physiologic parameters [7] or in response to triggers. Polymorphisms exist for substrains of the same inbred strains [8]. Genetic background also influences pathways that regulate thrombosis and hemostasis: differences were observed in global bleeding and thrombosis assays [9], coagulation and fibrinolytic factors [10], and susceptibility to treatment [11].…”
mentioning
confidence: 99%